Implementacija projekta Knjižnice čustev v Mestni knjižnici Kranj – izkušnje in izzivi - Štefe, Manca (Organizacija znanja, 2024)
Kranj City Library is the central regional library, which, among other things, implements programs for reading literacy, information literacy, lifelong learning and intergenerational cooperation. In this context, we joined the international project Libraries of Emotions with the aim of introducing an innovative reading promotion service. In the paper, the project and the process of implementing practical content were presented. First of all, we were interested in the efficiency and effectiveness of placing the physical collection of the Library of Emotions in our premises and the general response of users. Since the central theme of the project was the role of emotions in reading and their impact on individuals, we conducted eight bibliotherapy sessions and the reading campaign »Read with Emotions« for this purpose. The results showed that both the physical collection and the meetings centered around the books were extremely well received and that the Libraries of Emotions undoubtedly represent a fresh and innovative way of promoting reading in public libraries.
Keywords: biblioterapija; bibliotherapy; čustva; emotions; Knjižnice čustev; Kranj City Library; Libraries of Emotions; Mestna knjižnica Kranj; project; projekt